2018
DOI: 10.1017/s1041610218001370
|View full text |Cite
|
Sign up to set email alerts
|

Is the Montreal Cognitive Assessment (MoCA) screening superior to the Mini-Mental State Examination (MMSE) in the detection of mild cognitive impairment (MCI) and Alzheimer’s Disease (AD) in the elderly?

Abstract: Objective:To compare the accuracy of Mini-Mental State Examination (MMSE) and of the Montreal Cognitive Assessment (MoCA) in tracking mild cognitive impairment (MCI) and Alzheimer’s Disease (AD).Method:A Systematic review of the PubMed, Bireme, Science Direct, Cochrane Library, and PsycInfo databases was conducted. Using inclusion and exclusion criteria and staring with 1,629 articles, 34 articles were selected. The quality of the selected research was evaluated through the Quality Assessment of Diagnostic Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
206
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(260 citation statements)
references
References 69 publications
11
206
0
2
Order By: Relevance
“…These results largely align with previous studies showing no significant behavioral differences in cognitive performance on the basis of APOE4 status in younger (Taylor et al, 2017) and healthy older adults of similar demographic background (Reas et al, 2019), as well as our previous work using a similar episodic memory task in middle-aged adults at risk of AD (Rajah et al, 2017). However, given the high sensitivity of the MoCA for detecting mild cognitive impairment (Pinto et al, 2019), lower MoCA performance among -APOE4 participants may support theories suggesting that carrying an APOE4 allele may paradoxically benefit cognitive function in early and midlife (Evans et al, 2014). The majority of participants in both groups scored well above the cutoff of 26, argued by some to be overly conservative even in highly educated older adults (Elkana, Tal, Oren, Soffer, & Ash, 2019),…”
Section: Few Behavioral Group Differencessupporting
confidence: 91%
“…These results largely align with previous studies showing no significant behavioral differences in cognitive performance on the basis of APOE4 status in younger (Taylor et al, 2017) and healthy older adults of similar demographic background (Reas et al, 2019), as well as our previous work using a similar episodic memory task in middle-aged adults at risk of AD (Rajah et al, 2017). However, given the high sensitivity of the MoCA for detecting mild cognitive impairment (Pinto et al, 2019), lower MoCA performance among -APOE4 participants may support theories suggesting that carrying an APOE4 allele may paradoxically benefit cognitive function in early and midlife (Evans et al, 2014). The majority of participants in both groups scored well above the cutoff of 26, argued by some to be overly conservative even in highly educated older adults (Elkana, Tal, Oren, Soffer, & Ash, 2019),…”
Section: Few Behavioral Group Differencessupporting
confidence: 91%
“…Among the above four scales, MoCA and MMSE were not only widely used but also recognized as efficient tests for cognition impairment probing; it has been widely reported that MoCA is superior to MMSE in discriminating between MCI and healthy individuals [31][32][33]. For dementia cases, MoCA and MMSE were similar, but MoCA distributes MCI cases across a broader score range with less ceiling effect [34].…”
Section: Discussionmentioning
confidence: 99%
“…The MoCA is a 30-point test that takes 10 min and evaluates aspects of attention, concentration, orientation, calculation, language, verbal memory, recall, abstraction, visual-spatial ability, and EF. The Spanish version was used [30] and a cut-off score < 21 indicates MCI [30][31][32] Trail-Walking Test The Trial-Walking Test (TWT) is an ambulatory test in which the participants walk as rapidly as possible through 15 numbered flags in ascending order. The flags are installed randomly at each of the 15 positions in a 25-m 2 area (5 × 5 m), according to the procedure used by Yamada and Ichihashi [33].…”
Section: Cognitive Measuresmentioning
confidence: 99%